The Impact of Cholesterol Disorders and their Pharmacotherapy on Oral Health and Oral Healthcare: A Narrative Review - Darwazeh, Azmi; Al-Shorman, Hisham; Darwazeh, Tamer (Jordan Medical Journal, 2025)
Hypercholesterolemia (HC) or dyslipidemia is a common metabolic disorder estimated by WHO to affect 39% of the population globally. Some oral diseases or conditions, such as gingivitis or periodontitis, lichen planus, and recurrent aphthous ulceration, are believed to be more common among hypercholesteremic patients. HC may adversely affect the prognosis of dental implants, promote periapical periodontitis, and increase pulp chamber calcification, while hypocholesterolemia may be linked to oral cancer or potentially malignant disorders. Statins, mainly atorvastatin, prescribed for managing HC have antimicrobial effects and have been suggested as a promising pulp capping agent in vital pulp therapy. It also promotes periodontal regeneration, wound healing, improves oral cancer prognosis, and increases dental implant success rate. It may aid in managing minor recurrent aphthous ulcers and arthritis in TMJs. Adverse oral effects of statin therapy include increasing pulp calcification, lichenoid eruption, and xerostomia. The ability of simvastatin to reduce the osteoclastic, and increase osteoblastic activity of bone is rendering the patients susceptible to medication-related osteonecrosis of jaws. General dental practitioners and oral health workers should be aware of the oral manifestations of HC and statin therapy for better and safer management of their dental patients.